2010
DOI: 10.1021/es101131h
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Chemical Investigation and Experimental Verification on the Aquatic Photochemistry of the Sunscreen 2-Phenylbenzimidazole-5-Sulfonic Acid

Abstract: For ecological risk assessment of the large and ever-increasing number of chemical pollutants, it is of importance to develop computational methods to screen or predict their environmental photodegradation behavior. This study developed a computational method based on the density functional theory (DFT) to predict and evaluate the photodegradation behavior and effects of water constituents, taking a sunscreen and personal care product 2-phenylbenzimidazole-5-sulfonic acid (PBSA) as a model compound. Energy and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
160
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(167 citation statements)
references
References 60 publications
6
160
0
1
Order By: Relevance
“…The roles of ROS were examined using deuterium oxide (D 2 O, 70 mM) (Scharffetter-Kochanek et al, 1993) and tertiary butanol (tBuOH, 500 mM). D 2 O was used to prolong the lifetime of 1 O 2 in order to promote the oxidation involving 1 O 2 (Wilkinson et al, 1995;Zhang et al, 2010). tBuOH was employed as triplet state scavenges in addition to being a scavenger of OH which may be generated from O À$ 2 during a series of reactions (Benitez et al, 2013;Chen et al, 2008;Li et al, 2011).…”
Section: Photodegradation Kineticsmentioning
confidence: 99%
“…The roles of ROS were examined using deuterium oxide (D 2 O, 70 mM) (Scharffetter-Kochanek et al, 1993) and tertiary butanol (tBuOH, 500 mM). D 2 O was used to prolong the lifetime of 1 O 2 in order to promote the oxidation involving 1 O 2 (Wilkinson et al, 1995;Zhang et al, 2010). tBuOH was employed as triplet state scavenges in addition to being a scavenger of OH which may be generated from O À$ 2 during a series of reactions (Benitez et al, 2013;Chen et al, 2008;Li et al, 2011).…”
Section: Photodegradation Kineticsmentioning
confidence: 99%
“…The transient spectra of 500 mM PPB with 1 mM N 3 À , CO 3 2À , and Cl À were recorded in an acetonitrile-H 2 O solution (volume fraction 9:1, Figure 5) , and Cl À , respectively. The results clearly showed that 3 PPB Ã could be scavenged by anions, probably via an electron donation mechanism ( Figure 6) [27].…”
Section: Ppbmentioning
confidence: 95%
“…The PPB •þ and PPB-H • would not be eliminated by O 2 , which could even enhance the yield of radical cations by acting as the electron acceptor if the reactions really 3 PPB Ã also explained the negative effect of HA on the photochemical degradation of PPB. The energy gap for the excited triplet state of PPB ( 3 PPB Ã ) was calculated to be 3.352 eV, which is much higher than the energy gap for dissolved organic matter (2.233-2.597 eV) [27]. According to the Sandros equation [28], the quenching rate constant by energy transfer from 3 PPB Ã to dissolved organic matter is very close to the diffusion control rate constant.…”
mentioning
confidence: 92%
“…Hence, quantitative structure-activity relationship (QSAR) is suggested to model and predict the binding affinities of ligands to AhR by the new EU chemicals legislation REACH (European Commission, 2002), which has been successfully used to predict the toxicity of hydroxylated and quinoid PCB metabolites (Niu et al, 2007), endocrine disrupting activities (Li et al, 2010a(Li et al, , 2010b and photoinduced toxicity (Wang et al, 2009a,b;Zhang et al, 2010) of organic compounds. Bandiera et al (1983) developed linear free-energy relationships involving substituent constants and indicator variable for PCBs affinity data, and concluded that polarizability and electron-acceptor properties of the ligands can control the affinity of PCBs binding to the AhR.…”
Section: Introductionmentioning
confidence: 99%